Learning by doing a pokolenie Z na przykładzie realizacji projektu „UPoluj kulturę!” - Król, Magdalena B. (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The article addresses the issue of academic education of the Generation Z, which will be the recipient of the educational offer of universities in the coming years. It presents the results of own research, which attempted to find the answer to the question - are active teaching methods more suited to the educational needs of the Generation Z than traditional methods? The specific features of the Generation Z as well as the dynamically changing environment, especially information and technology, requires a different approach to the teaching process. Shifting the focus from feeding methods to active ones seems to be inevitable, and a flexible approach in this area becomes both a need and a necessity.